Acute Myeloid Leukemia Presenting as a Posterior Fossa Tumor. Issue 7 (October 2021) - Vanan, Magimairajan Issai; Li, Jie; Bunge, Martin; Serletis, Demitre; Almiski, Muhamad; Israels, Sara J.
Abstract : Extramedullary leukemia in pediatric acute myeloid leukemia can manifest as a myeloid sarcoma (MS), also known as granulocytic sarcoma or chloroma, in a variety of sites, or as leukemic blasts in the cerebrospinal fluid. Isolated MS of the central nervous system is rare. We report a case of acute myeloid leukemia with central nervous system-MS presenting as a posterior fossa mass mimicking a primary intracranial tumor.